Praktik Pengawasan Pengelolaan Keuangan Sekolah - Sri Rahayu; Mukhzarudfa; Yuliusman; Yuliana (Jurnal Akuntansi & Keuangan Unja, 2019)
ABSTRACT The purpose of this research to uncover the practice of supervision on school financial management. The data used in the form of primary to be collected through the questionnaire and in-depth interviews. Respondents and informants of this study were school principals and supervisors. Quantitative and qualitative research methods were used in this study. The results of the research show that supervision at the planning and implementation stage is very good, as evidenced by the involvement of stakeholders in the preparation of school plans, although with different patterns. Supervision at the reporting and accountability stage are still at a good position. The role of supervisor is very needed in supervising school financial management. Supervisory competence regarding financial management must be improved through training, socialization and technical guidance. Keywords : School , supervision , efficiency and effective ABSTRAK Tujuan penelitian ini untuk mengungkap praktik pengawasan pengelolaan keuangan sekolah. Data yang digunakan berupa data primer yang akan dikumpulkan melalui kuesioner dan wawancara mendalam. Responden dan informan penelitian ini adalah kepala sekolah dan pengawas sekolah. Metode penelitian kuantitatif dan kualitatif digunakan pada penelitian ini. Hasil riset menunjukkan pengawasan pada tahap perencanaan dan pelaksanaan sangat baik, terbukti dengan keterlibatan stakeholders dalam penyusunan rencana sekolah, walaupun dengan pola yang berbeda-beda. Pengawasan pada tahap pelaporan dan pertanggungjawaban masih berada pada posisi baik. Peran pengawas sangat dibutuhkan dalam pengawasan pengelolaan keuangan sekolah. Kompetensi pengawas tentang pengelolaan keuangan harus ditingkatkan melalui pelatihan, sosialisasi dan bimbingan teknis. Kata Kunci : Sekolah, Pengawasan, efisiensi dan efektif.